Kajian pengesanan graduan - Abd Karim Mohd Mustamam, Nordin Abu Bakar, Ibrahim Mohamad, Buyong Kahar Mohd Ramli (Universiti Pendidikan Sultan Idris, 2006)
Kajian pengesanan graduan by Abd Karim Mohd Mustamam, Nordin Abu Bakar, Ibrahim Mohamad, Buyong Kahar Mohd Ramli,